Bibliometric Analysis of Trash Management and Ecological Footprint in Super-Priority Destinations - Judijanto, Loso (West Science Interdisciplinary Studies, 2025)
Tourism growth in environmentally sensitive areas, such as Indonesia’s Super-Priority Tourism Destinations (SPTD), has heightened concerns over trash accumulation and ecological degradation. This study presents a bibliometric analysis of global scholarly literature on trash management and ecological footprint within tourism contexts, aiming to map research trends, thematic clusters, and collaboration networks. Using data from the Scopus database (2000–2024) and analyzed through VOSviewer, the study identifies dominant keywords including ecological footprint, sustainable development, tourist destination, and carbon footprint—indicating a strong emphasis on sustainability metrics in tourism research. Co-authorship and institutional mapping reveal the pivotal role of cross-national collaboration, with China, Italy, and the United Kingdom among the most active contributors. The overlay visualization highlights a temporal shift from foundational themes (e.g., environmental impact) toward more integrated topics (e.g., tourism management and sustainability governance). These findings offer practical implications for policymakers and stakeholders involved in destination management, especially in formulating data-driven, interdisciplinary strategies for reducing tourism’s ecological impact. The study also contributes to the theoretical consolidation of tourism-environment linkages by providing a structured research roadmap and identifying potential areas for future investigation.